FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN - Hidayat, Ruben; Setijaningsih, Herlin Tundjung (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study sought to ascertain the effects of firm size and leverage on the financial performance of Indonesian food and beverage subsector companies listed on the IDX from 2019 to 2021. This research was conducted with a total of 54 samples consisting of 18 Indonesian food and beverage subsector companies listed on the IDX from 2019 to 2021. The processing of research data uses the Microsoft Excel and Eviews applications version 12.0. The findings demonstrated that firm size had a positive and significant effect on financial performance, while leverage had a negative and significant effect. The findings of this study suggest that in order to improve financial performance, firms must reduce their use of leverage and grow in size, which will send a positive signal to those who are interested.